La jeunesse des varoş d’Istanbul et des quartiers dits « sensibles » en banlieue parisienne - Mustapha Poyraz (Sociétés et Jeunesses en Difficulté)
This article compares the distinct modes of living and ‘acting’ among youth groups in two distinct socio-economic contexts: the quartiers sensibles (or hot spots) of Ile de France and Istanbul varoş. The distinct levels of economic development and of social protection allow us to assess this comparative approach. Religion and politics also tend to influence the attitudes of the young people. Whilst the French youth in the suburbs is marked by a radical political and urban cleavage, the varos ‘ youth tend to profit from very rich and mobilising political and relational networks. However, in the Turkish context, the absence of economic and social support ‘institutions’ promoted by the State and the local authorities has increased the despondence of the youg groups. Since a quarter of a century, French public institutions have not stopped the closure of the youth groups in their quartiers sensibles. In both situations, religion is increasingly seen as a ‘moderating’ factor.This comparison should allow us to understand the impact of the urban contexts, of the political and religious networks as well as the influence of public institutions on the groups of these two distinct contexts. This research has been undertaken during several years in different quartiers sensibles of the Parisian region and those of the Istanbul varoş.